The mean fluorescence intensities of anti‐HLA antibodies detected using micro‐bead flow cytometry predict the risk of platelet transfusion refractoriness. (8th May 2013) - Beligaswatte, Ashanka; Tsiopelas, Eleni; Humphreys, Ian; Bennett, Greg; Robinson, Kathryn; Davis, Ken; Bardy, Peter
Summary: There are no accepted methods to predict the development of platelet transfusion refractoriness (PTR) due to human leucocyte antigen (HLA)‐alloimmunization. Hence, matched platelets are usually given only to patients demonstrating PTR, necessarily resulting in some ineffective random donor platelets (RDPLT) transfusions. To assess its utility in predicting PTR, we retrospectively tested samples from 387 patients receiving chemotherapy for acute leukaemia or autologous transplantation using a micro‐bead flow cytometry assay. The average of the mean fluorescence intensities (avgMFI) of the class I beads in the screening assay was correlated with outcomes of RDPLT transfusions during a 2 week period. Antibodies were detected in 57 patients; 66 developed PTR, of whom 28 were alloimmunized. avgMFI usefully predicted the development of PTR (area under the receiver operating curve 0·87, 95% confidence interval: 0·77–0·96). A logistic regression model estimated the probability of PTR to be >90% when avgMFI >5440. These results indicate that micro‐bead flow cytometry assays could inform a risk‐adapted strategy for managing thrombocytopaenic HLA allo‐immunized patients.